Radial junction solar cells prepared on single crystalline silicon wafers by metal‐assisted etching (Phys. Status Solidi RRL 5/2017). Issue 5 (May 2017) - Baytemir, Gulsen; Es, Firat; Alagoz, Arif Sinan; Turan, Rasit
Abstract : Radial junction solar cell has been proposed as an alternative device geometry to conventional planar solar cells with its remarkable electrical and optical performance. In this geometry, micro/nano pillars on the surface allow minority carrier collection in the radial direction and shorten the carrier diffusion length. Moreover, increased light trapping in the pillars and reduced reflection from surface enhance the solar cell efficiency. In their letter (article no.1600444 ) Baytemir et al. have investigated radial junction solar cells which have different micropillar length to observe the effect of micropillar length on optical and electrical performance of the solar cells. Photolithography and metal assisted etching (MAE) techniques have been used to form well‐ordered silicon micropillar arrays, and different length of micropillars has been obtained by changing metal assisted etching time. It is observed that etching time and micropillar length are directly proportional. Moreover, both reflection and J sc results show that optical absorption increases with increasing micropillar length. However, surface area and deteriorations on the surface increase with etching time. Therefore, there is still room to improve the solar cell efficiency with a proper passivation scheme.